The Semantics of Place Names: A Reflection of Cognition and Linguistic Heritage of Speakers: (Semantik Nama Tempat: Gambaran Kognisi dan Warisan Bahasa Penutur) (Jurnal Bahasa, 2018)
The names of the various natural features of the topography within a geolinguistic domain are the result of the perception of the language speakers native to that particular area. Entities that exist in their surroundings are identified through a process in which the specific topographical features of the area are abstracted and then labelled using sound images. These labels are the device by which these entities enter the collective memory of the community of the area. Place names reflecting local flora and fauna are examples of such labels. Applying the theories of sign, abstraction, entity and historical linguistics, this article discusses the role of place names in interpreting the historical developments as well the migration and settling of the various indigenous groups of Malaysia.Kata kunci: entity, sound image, abstraction, perception, extentional meaning, intentional meaning